PENGEMBANGAN BAHAN AJAR FISIKA BERBASIS LKM CERIA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIF MAHASISWA CALON GURU FISIKA - Verawati, Ni Nyoman Sri Putu; Kosim, Kosim; Gunawan, Gunawan; ‘Ardhuha, Jannatin; Arizona, Kurniawan (Lensa : Jurnal Kependidikan Fisika, 2017)
The purpose of this research is to develop CERIA LKM-based physics teaching materials to improve critical thinking skills and creative student physics teacher candidate. This research is a development research that fulfill 3 (three) criteria, namely validity (valid), practicality (practical), and effectiveness (effective). Assessment of valuator on the validation stage of basic physics teaching materials based on MFI Ceria developed is 3.37 (good category) with reliability percentage 97.76% (categorized reliable). The results of this validation indicate that the basic physics materials based on Ceria MFIs developed are feasible to be used in the implementation stage. The implementation phase of teaching materials has involved physics education program students, where the results of the implementation of teaching materials developed categorized 'very good'. The next implementation is the evaluation of students' critical and creative thinking skills.